Hubungan Indeks Massa Tubuh (IMT) dengan Range of Motion (ROM) Articulatio Talocruralis pada Lansia - Gracela M. Siada; Jimmy F. Rumampuk; Fransiska Lintong (Jurnal Biomedik:JBM, 2024)
Abstract: Joint Range of Motion (ROM) values indicate the flexibility of the respective joints. An increase in Body Mass Index (BMI) is one of the factors that can lead to a decrease in ROM values, consequently affecting muscle strength and joint functionality. Several studies have established a connection between increased BMI and reduced ROM, particularly in populations with obesity, where ROM tends to be more limited compared to non-obese populations. This research aims to explore the relationship between Body Mass Index (BMI) and the Range of Motion (ROM) of the articulatio talocruralis in the elderly population of Wioi Village, Minahasa Tenggara Regency. This study adopts an analytical observational approach with a cross-sectional design. The tools utilized in this research include digital scale and stature meter for BMI measurement, and goniometer for ROM measurement. The research sample was selected using simple random sampling technique. Data analysis was conducted using the Spearman correlation test. Among the 51 respondents examined, the Spearman correlation analysis revealed a significant negative relationship between BMI and Dorsiflexion (p= 0.004, r= -0.397) and Plantarflexion (p= 0.001, r= -0.435). In conclusion, there is a significant association between Body Mass Index (BMI) and the Range of Motion (ROM) of the articulatio talocruralis in the elderly population of Wioi Village, Minahasa Tenggara Regency. Keywords: body mass index (BMI); range of motion (ROM); articulatio talocruralis; elderly   Abstrak: Nilai ROM sendi menunjukkan fleksibilitas sendi tersebut. Peningkatan nilai IMT merupakan salah satu faktor yang dapat menyebabkan nilai ROM menurun dan akan mempengaruhi kekuatan otot dan sendi. Beberapa penelitian menghubungkan peningkatan IMT dengan penurunan ROM dimana populasi dengan obesitas memiliki ROM yang terbatas dibandingkan dengan populasi yang tidak mengalami obesitas. Penelitian ini bertujuan untuk mengetahui hubungan antara indeks massa tubuh (IMT) dengan range of motion (ROM) articulatio talocruralis pada lansia di Desa Wioi, Kab. Minahasa Tenggara. Penelitian ini merupakan penelitian observasional analitik dengan pendekatan potong lintang (cross sectional). Instrumen yang digunakan pada penelitian ini adalah timbangan digital dan stature meter untuk mengukur IMT, dan goniometer untuk mengukur ROM. Sampel penelitian dipilih dengan teknik simple random sampling. Analisis data dilakukan menggunakan uji korelasi spearman. Dari 51 responden yang diteliti, analisis korelasi spearman menunjukkan adanya hubungan negatif yang bermakna antara IMT dengan Dorsofleksi (p = 0,004, r = -0.397) dan Plantarfleksi (p = 0,001, r = -0,435). Sebagai simpulan, terdapat hubungan antara Indeks Massa Tubuh (IMT) dengan Range of Motion (ROM) articulatio talocruralis pada lansia di Desa Wioi, Kab. Minahasa Tenggara. Kata Kunci: indeks massa tubuh (IMT); range of motion (ROM); articulatio talocruralis; lansia